Cardiovascular outcomes associated with SGLT2 inhibitor therapy in patients with type 2 diabetes mellitus and cancer: a systematic review and meta-analysis - Kuo, Hsiao-Huai; Wang, Kuang-Te; Chen, Hsin-Hao; Lai, Zih-Yin; Lin, Po-Lin; Chuang, Yung-Jen; Liu, Lawrence Yu-Min (Diabetology and metabolic syndrome, 2024)
Background Cancer patients with diabetes are at increased risk for cardiovascular diseases due to common risk factors and well-documented drug-associated cardiotoxicity. Sodium-glucose cotransporter-2 (SGLT2) inhibitors have shown cardiovascular benefits in patients with diabetes, but their effects on cancer patients remain unclear. This study aimed to evaluate the cardiovascular outcomes associated with SGLT2 inhibitor therapy in patients with concomitant diabetes and cancer. Methods We conducted a systematic review and meta-analysis of cohort studies comparing cardiovascular outcomes between cancer patients with diabetes receiving SGLT2 inhibitors and those not receiving SGLT2 inhibitors. PubMed, Embase, and the Cochrane Library were searched from inception to February 29, 2024. The primary outcome was all-cause mortality, and the secondary outcomes were heart failure hospitalization, and adverse events. Random-effect models were used to calculate pooled risk ratios (RR) with 95% confidence intervals (CI). Subgroup and sensitivity analyses were conducted to identify potential sources of heterogeneity and explore the effect of SGLT2 inhibitors on mitigating cardiotoxicity. Results Nine cohort studies involving 82,654 patients were included. SGLT2 inhibitor use was associated with a significantly lower risk of all-cause mortality (RR 0.46, 95% CI 0.31–0.68, P < 0.0001; I 2 = 98%) and heart failure hospitalization (RR 0.49, 95% CI 0.30–0.81, P = 0.006; I 2 = 21%) compared to non-use. The mortality benefit remained significant in patients receiving anthracycline chemotherapy (RR 0.50, 95% CI 0.28–0.89, P = 0.02; I 2 = 71%). SGLT2 inhibitor use was also associated with a lower risk of sepsis (RR 0.32, 95% CI 0.23–0.44, P < 0.00001; I 2 = 0%) and no increased risk of diabetic ketoacidosis (RR 0.66, 95% CI 0.20–2.16, P = 0.49; I 2 = 0%). Conclusions SGLT2 inhibitor therapy is associated with lower risks of all-cause mortality and heart failure hospitalization in patients with concomitant diabetes and cancer. These findings suggest that SGLT2 inhibitors may offer cardiovascular benefits in this high-risk population. Randomized controlled trials are needed to validate these findings and evaluate the safety and efficacy of SGLT2 inhibitors in specific cancer types and treatment regimens.